Sick and Cold? Evidence on the Dynamic Interplay between Energy Poverty and Health - Santiago Budría; Paolo Li Donni; Eugenio Zucchelli (Institute of Labor Economics (IZA), 2025)
Energy poverty and health appear to be closely related, yet robust evidence on whether and how they mutually influence each other over time is still limited. We employ a dynamic latent class model on rich longitudinal data from the Household, Income, and Labor Dynamics in Australia Survey to uncover patterns of dynamic interdependence between energy poverty and ill-health. Our approach integrates key modelling features, such as state dependence and time-varying unobserved heterogeneity, while also revealing and quantifying mechanisms of joint dependence over time. Unlike previous studies, our model shows that although energy poverty and ill-health seem to mutually influence each other, the effect of ill-health on energy poverty appears to be comparatively larger, suggesting that ill-health might be a stepping stone to energy poverty. In addition, we identify three main types of individuals corresponding to different socioeconomic profiles and varying levels of vulnerability to changes in energy prices. These findings may indicate the need for targeted interventions rather than exclusive reliance on energy subsidies.
Keywords: C33; C35; I31; I32; 330; energy poverty; health; dynamic latent class models; HILDA